If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 8) = 12 Reorder the terms: 2(8 + x) = 12 (8 * 2 + x * 2) = 12 (16 + 2x) = 12 Solving 16 + 2x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + 2x = 12 + -16 Combine like terms: 16 + -16 = 0 0 + 2x = 12 + -16 2x = 12 + -16 Combine like terms: 12 + -16 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| x^2+5x=204 | | 32=4t | | 12y-16=-4y+48 | | (x^2)-15=2x | | 20=4y | | 2(3x+2)-x+5=19 | | -3(3p+17)=-5 | | 3x+(5x-3)=7 | | 3(2x-5)+6(x+2)= | | 5x+3=x+31 | | 3+.5x=17-3x | | lx+6l=9 | | -4=w-30 | | 10+2x=15+1x | | 8y-3=6y+7 | | 96+12x+30=180 | | x*5-2x=38 | | a+5a=2a+9 | | A=.05bcd+bc | | 4+5x=x+23 | | t+28=13 | | a+5a=2a+a | | -6-3=3x+6-6 | | 1y-2=.33(y+6) | | 9=9-8h | | 5x-1y=15 | | 48+4y-18=14y-12-4y | | X+24=32X | | 3a^2+9a+12=0 | | 4k+8-6k= | | x+x=6+2 | | r(r+3)=0 |